Two-production-period in a duopoly with nonprofit and for-profit firms - Ferreira, Fernanda A. (2014)
We investigate endogenous roles in a competition between a nonproﬁt ﬁrm and a for-proﬁt ﬁrm in a homogeneous goods market, by allowing two production periods. We ﬁnd that the Cournot-type equilibrium and one Stackelberg-type equilibrium where the nonproﬁt ﬁrm becomes the follower exist; however, another tackelberg-type equilibrium where the nonproﬁt ﬁrm becomes the leader does not exist.